Capital market equilibrium and efficiency : implications for accounting, financial, and portfolio decision making - Bicksler, James L. (Lexington: Lexington Books, 1977)
This book attempts to communicate the central ideas, results, and implications of both the efficient markets and capital asset pricing models.
osc 11/05/2018
Loans
Keywords: Capital; Investments; Capital assets pricing model; Finance